Traditional Mamasa rice barn architecture - Lullulangi, Mithen (2024)
This research aims to determine the architecture of traditional rice barns (Alang) in Mamasa, West Sulawesi, as one of the traditional architectural products that has high cultural value. This research is qualitative in nature. Data collection methods are through interviews, field observations, and documentation. The data analysis technique used is qualitative analysis, namely data collection, data presentation, data reduction, and drawing conclusions. The results of the research show that the architecture of traditional rice barns (Alang) in Mamasa can be classified based on the number of Banga (palm tree poles) into several categories: 1) Alang 4 banga, 2) Alang 6 banga, 3) Alang 8 banga, 4) Alang 12 banga. Then in terms of color, it can be classified into three types: 1) Alang ordinary (Natural color), 2) Alang Bolong (Black color), and 3) Alang Sura' (Painting Color).